Rising Inequality or Regional Strength? Investigating Income Growth Divergence among BRICS Nations - Ncwadi, Ronney (International Journal of Economics and Financial Issues, 2025)
This paper examines income growth dynamics in BRICS economies (1991–2022) using panel data and random-effects estimation. It tests the income convergence hypothesis by analyzing GDP per capita growth and key drivers such as investment, FDI, technology, trade, and education expenditure. Contrary to β-convergence theory, findings show income divergence: higher-income BRICS countries, especially China and India, grow faster than their lower-income peers. The study quantifies divergence speed and illustrates widening income gaps, underscoring the need for structural reforms, innovation-driven investment, and regional cooperation. It also calls for further research accounting for cross-sectional dependence and country- specific heterogeneity.